Folding techniques for designers : from sheet to form - Jackson, Paul, 1956- (Laurence King Pub., 2011)
This unique, practical handbook explains the key techniques of folding, such as pleated surfaces, curved folding, and crumpling. It covers more than 70 techniques explained by clear step-by-step drawings, crease pattern drawings, and specially commissioned photography.